Systemic Mastocytosis: Following the Tyrosine Kinase Inhibition Roadmap - Piris-Villaespesa, Miguel; Alvarez-Twose, Ivan (Frontiers in Pharmacology, 2020)
Systemic mastocytosis is a rare and heterogeneous disease characterized by mast cell proliferation and activation. KIT is a transmembrane tyrosine kinase which plays a key role in mast cell growth, differentiation and survival. After interaction with its ligand, the stem cell factor, KIT dimerizes activating downstream pathways involving multiple tyrosine kinases (PI3K, JAK/STAT, RAS/ERK). Activating mutations in KIT are detected in most cases of systemic mastocytosis, being the most common KIT D816V. Therefore, since the emergence of tyrosine kinase inhibitors, KIT inhibition has been an attractive approach when facing mastocytosis treatment. Initial reports showed that only the rare KIT D816V negative cases were responsive to ITKs. However, the development of new TKIs such as midostaurin or avapritinib with activity against mast cells carrying the D816V KIT mutation, has changed the landscape of this disease.